KEBIASAAN JAJAN DI SEKOLAH DAN MAKAN DI RUMAH TIDAK BERHUBUNGAN DENGAN STATUS GIZI ANAK USIA SEKOLAH - Lydia fanny; intan dwi dili Fitria; sirajuddin Sirajuddin; Hendrayati Hendrayati (Media Gizi Pangan, 2017)
Backgrounds: Snacking is a common habits while an appetite is a desire to eat or feeling hungry. The student ususally prefer choose snacking and less interest with the meal serve at home. Snacking habits which less in fulfill healthy and nutrition requirement also decrease of appetite will threatening the healthy and nutrition status of the student.Objectives: This research aims to understanding the relation of snacking habits and appetite with the nutrition status of students in Paccerakkang State Elementary School, Biringkanaya, Makassar.Methods: This research using observasional method with cross sectional research design. The sample are student in grade IV and V choosing by random sampling. To find the relation between variable using Chi Square examination.Results: The results of this research shows that snacking habits tend to not good (52,0%). The appetite of students tend to good (52,0%). The nutrition status category of the students tend to normal (78,0%).Conclusions: There are nothing siginificance relation between snacking habits with student nutritions status in Pacerakkang State Elementary School, with value of p = 0,560 (>0,05).Keywords : Snacking habits, appetite, nutrition status, students